The labor theory of value strikes back: ULC + the method for measuring the level of national competitiveness - Marko Djogo (Journal of Contemporary Economic and Business Issues, 2019)
National competitiveness, macro-competitiveness, and competitiveness of states; those seemingly simple and common terms, are actually highly controversial. The interpretation of historical backgrounds and basic postulates which have been the foundations of methods for the measurement of macro-competitiveness since the 1970s to the present, is a matter of interest in the first part of this paper. Just after this, we will provide critical observations on methods used so far - which is necessary if we want to make a contribution to the further development of theory (and practice). The second part of this work, which is smaller in quantity but larger in quality, is committed to the development of the theoretical foundation for the development of the new fourth generation of methods for measurement of macro-competitiveness. We entitled this method ULC + the method for measurement of national competitiveness and it is based on the synthesis of Michael Porter's idea that productivity is a synonym for competitiveness and the direct (outputs) methods for measurement of national competitiveness. We have done this by using working hours as a common measuring unit which would enable us to sum "apples and oranges", meaning the cost of labor and the cost of capital.
Keywords: E20; F40; 330; national competitiveness; methods for measurement; synthesis